The effect of plasticizers on rheological, physical and mechanical properties of low cement high alumina gunning refractories - Mohammad Mobasheri; Ali Mohammad Hadian; Yasaman Mohammadi; Behzad Azimi; Mehrnoosh Kamali (Scientific Reports)
Abstract In this research, the effect of different plasticizers with different amounts on the properties of monolithic alumina-based refractories has been investigated. All samples were fired at 1100 °C and 1550 °C. In order to evaluate the desired properties, first the rheological properties of the samples were examined, and then for further investigations, loss on ignition (LOI), percentage of permanent linear changes (PLC), apparent porosity (AP), bulk density (BD) and cold crushing strength (CCS) tests were used. In addition, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffractometry (XRD) were used to characterize the samples. 1 and 2 wt% of CMC, H19, bentonite and ballclay were added to the mixtures as plasticizers. The results of this research showed that the sample containing 1 wt% of ball clay can be the most appropriate one due to its highest strength, highest density and lowest apparent porosity. Moreover, the sample containing 2 wt% of H19 (a commercially available binder) has the optimum properties because of its highest strength for the samples fired at 1100 °C. For the mixtures fired at 1550 °C, the more amount of silica has caused higher cold crushing strength due to the presence of the low melting point phases which are not desired and therefore, the mixtures with less silica can be used.